The Relationship between Ulama and the State in the Political Thought of KH. Moenawar Chalil (1952-1961) - Rizki Mulyana; Ading Kusdiana; muhammad riza (Universitas Negeri Makassar, 2026)
This article analyzes the relationship between ulama and the state in the political thought of K.H. Moenawar Chalil (1908–1961), an Indonesian Muslim scholar and intellectual who was active during the Liberal Democracy period of the 1950s. Using the historical research method and Abul A'la Al-Maududi's concept of theo-democracy as an analytical framework, this study reconstructs Moenawar Chalil's thought based on primary sources comprising his writings in various Islamic periodicals and two major books. The findings reveal three key points. First, Moenawar Chalil positioned ulama as an independent moral authority responsible for overseeing state power, not as part of the governmental apparatus. Second, in his view, obedience to rulers is conditional, applying only when leaders govern in accordance with Islamic law. Third, the principle of shura is an inseparable element of the ideal Islamic government he envisioned. This research contributes to filling a historiographical gap by offering a more comprehensive reconstruction of Moenawar Chalil's political thought, grounded in a thorough engagement with primary sources. Keywords : Moenawar Chalil, Ulama, State, Imamah, Theo-democracy, Indonesian political Islam